(3OQGSI aj GdEbJUGO GdOhdj ef efXhQ GbJUGOjGJ GdShb hGdJMQQ GdEbJUGOjs - (3eUWai QTOj(B, (3TjMIs ((3GdEScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI ddfTQ(B,s, 1998)
(3GdShb GdOhdjI(B- (3GdfXQjGJ hGdSjGSGJ GdJLGQjI(B- (3GdfXQjGJ GdeaSQI ddJLGQI GdYGdejI(B- (3GdSjGSGJ GdJLGQjI GdOhdjI(B- (3GdfXGe GdOhdj ddJLGQI GdYGdejIs
Keywords: (3GbJUGOjGJ GdShbs; (3GdEbJUGO GdOhdjs